Stopkontak Pintar Berbasis Internet of things sebagai Solusi Manajemen Energi Listrik dengan Menggunakan Aplikasi Android - Yandhika Surya Akbar Gumilang; Mokh Sholihul Hadi; Dyah Lestari (Universitas Merdeka Malang, 2022)
Leaving an electrical appliance connected to an outlet when not in use or on standby accounts for 80% of electricity wastage. A study conducted by the Lawrence National Laboratory, it was revealed that when a cellphone charger is still connected to a wall socket when not in use, there is still power being released. The purpose of this research is to make a smart socket based on the Internet of things (IoT) to be able to save electricity. An IoT smart socket that is designed to be integrated with an Android-based smartphone application. The IoT smart socket uses the ACS-712 current sensor and the ZMPT101B voltage sensor to measure electrical energy and then uses the Arduino Nano microcontroller and NodeMCU ESP8266 so that the socket can communicate with the Google Firebase cloud via Wi-Fi connection to the internet. The IoT smart socket uses a relay module as a switch, and the micro SD and RTC DS3231 modules record and store data (data logging) of electrical energy information that has been issued. The IoT smart outlet is integrated with Android smartphone applications created through Android Studio. The IoT smart socket in this study has 2 socket holes and features Wi-Fi pairing, electrical energy measurement, data logging, and socket scheduling (timer). The IoT smart outlet has an average measurement error of 3.27% when compared to a measuring instrument, and there is an error in the outlet timer feature with a delay of 5 to 30 seconds. The IoT smart socket is still said to be valid and can function properly.